Pengaruh Pendidikan, Penanaman Modal Asing, dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi di Provinsi Bali - cahya, Putu Novi; Indrajaya, I Gustu Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 2, Februari 2018 (pp. 212 - 380), 2018)
Development is a process of change towards a better and continuous direction to achieve the goal of realizing a just Indonesian society, foreign cultured, advanced and prosperous in the Unitary State of the Indonesia. Economic growth is indicator for successful development in a region. Economic development includes various aspects of forming such as economic, social, political and other in which these aspects are synergized to achieve the success of development both at the central and regional levels. The objectives the research to  achieved, among others, to know how the influence of education, foreign investment and labor simultaneously to economic growth in Bali and to know the effect of education, foreign investment and partial employment on economic growth in Bali . The data used are secondary data from 33 provinces in Indonesia 2011-2015. The data using panel data analysis with multiple linear regression model. Based on the result of research, using multiple linear regression analysis shows  the variables of education, foreign investment and labor have positive and significant influence simultaneously  economic growth in Bali. The variables of education, foreign investment and labor have a positive and partially significant impact economic growth in Bali. Keywords: Education, Foreign Investment, Manpower, Economic Growth